THE IMAGE OF WOMEN IN ANCIENT UZBEKISTAN: AN ANALYSIS OF ARCHAEOLOGICAL MONUMENTS AND CULTURAL-RELIGIOUS PERCEPTIONS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
this article analyzes the image of women in ancient Uzbekistan through archaeological monuments using a cultural and philosophical approach. Findings from sites such as Bolaliktepa, Fayaztepa, Karatepa, Ayritom, Afrasiab, and Koktepa reveal the religious, social, and aesthetic roles of women in ancient society. The study demonstrates that women were regarded not only as symbols of beauty but also as embodiments of protection, fertility, prosperity, and stability of life. These perceptions later influenced folklore traditions and became an integral part of national cultural heritage.